Bangka-culture-based descriptive reading materials for tour and travel in SMK: Students’ needs analysis - Nur Azizah; Rita Inderawati; Machdalena Vianty (English Review: Journal of English Education, 2020)
This research aimed to find out the Vocational High School (SMK) students' needs in English reading materials development based on Bangka local culture reviewed by students', teachers', and stakeholders' views. The data were obtained through the use of a questionnaire and semi-structured interviews. The data were analyzed both quantitatively and qualitatively. The result of the need analysis showed that: 1) English was important for the students mostly to support their future carrier, 2) students’ English proficiency was in the beginner level, 3) students still had some difficulties in reading comprehension, 4) the kind of text needed was a descriptive text, 5) the forms of questions mostly suggested were multiple choice and essay, 6) there was a need of integrating English reading materials with the materials of the content subjects, 7) students still lacked knowledge about Bangka local culture, 8) there were no existing English reading  materials which were integrated with Bangka local culture, 9) two main reasons of integrating Bangka local culture in reading, were enhancing the students’ knowledge about Bangka culture, and promoting their skills in their study program, 10) the aspects of Bangka local culture needed to be integrated into English reading materials were about arts, customs, foods, traditional clothes, traditional equipment, folklores, and historical places.  Due to the needs, it was necessary to develop supplementary descriptive reading materials by integrating Bangka local culture which matched the students’ English proficiency and could support their study program.